Combined In Silico and Experimental Investigations of Resveratrol Encapsulation by Beta-Cyclodextrin - Iskineyeva, A.; Fazylov, S.; Bakirova, R.; Sarsenbekova, A.; Pustolaikina, I.; Seilkhanov, O.; Alsfouk, A.A.; Elkaeed, E.B.; Eissa, I.H.; Metwaly, A.M. (Plants, 2022)
The results of the computational and the physicochemical studies of the encapsulation of resveratrol with -cyclodextrin are presented here. At first, the molecular docking experiments predicted good binding. Several MD simulations and MM-PBSA experiments confirmed the reliable binding, showing optimal kinetics and energy. As an application, resveratrol inclusion complexes with -cyclodextrin were obtained in an aqueous alcohol medium via microwave treatment. The results of thermographic measurements of the obtained clathrates using a differential scanning calorimeter are presented, and the obtained activation energy was calculated using the Ozawa–Flynn– Wall and Friedman methods, as well as nonparametric kinetics. The effect of complexation on the kinetic parameters of thermal destruction of the -cyclodextrin–resveratrol inclusion complex was considered. The morphology of the surface of the obtained clathrate complexes was described using a scanning electron microscope. The spectral properties of the inclusion complex were characterized by FT-IR, 1H, and 13C NMR spectroscopic data. The obtained in silico, morphological, thermogravimetric, and spectral results confirmed the formation of the resveratrol– -cyclodextrin complex. The antioxidant activities of the inclusion complex were determined to be 12.1 g/mL, compared to 14.3 g/mL for free resveratrol, indicating an improvement in the bioactivity.
Keywords: cyclodextrins; B -cyclodextrin; vitamin resveratrol; molecular modeling; inclusion complexes; antioxidant activity; clathrate